STUDI PENCEMARAN AIR PADA SAWAH TAMBAK AKIBAT PEMBERIAN PUPUK NPK (NITROGEN, PHOSPAT, KALIUM) DI KECAMATAN GLAGAH KABUPATEN LAMONGAN - Moch Saad; Nur Khasan Wakhid (Universitas Mataram, 2024)
Sustained provision of nitrogen, phosphate and potassium (NPK) fertilizers can have a negative impact on the environment and surrounding communities. This research aims to determine the status of water pollution and the suitability index of cultivated land in Glagah Subdistrict, Lamongan Regency. This research was carried out in March–May 2023 and was carried out in Glagah Subdistrict, Lamongan Regency. The sample collection method used in this research is to use a proportional sampling technique. Intuitive sampling of land suitability requires a matrix of characteristics of constructed pond land based on spatial criteria that have been adjusted to the characteristics and living conditions of fish. Meanwhile, to determine the level of pollution using the Family Biotic Index (FBI) method. The results of this research show the status of water pollution in pond rice fields due to NPK irrigation in Glagah Subdistrict, Lamongan Regency, which means that at station 1, station 1 obtained a result of 5.5 including the category of highwater quality or pollution with quite a lot of organic matter, station 2 obtained a result of 7. .2 including the buiruik water quality category or very much polluted organic matter, station 3 got a result of 6.7 including the buiruik water quality category or very much organic matter polluted. Meanwhile, the suitability index for cultivation land in pond rice fields in Glagah District, Lamongan Regecy shows that station 1, station 2 and station 3 are included in the conditional suitability criteria (S3).